The Role of Bioelectrical Impedance Analysis in Predicting COVID-19 Outcome - Stevanovic, Djordje; Zdravkovic, Vladimir; Poskurica, Mina; Petrovic, Marina; Cekerevac, Ivan; Zdravkovic, Nemanja; Mijailovic, Sara; Todorovic, Dusan; Divjak, Ana; Bozic, Dunja; Marinkovic, Milos; Jestrovic, Aleksandra; et al. (Frontiers in Nutrition, 2022)
Background: Published data regarding the impact of obesity on COVID-19 outcomes are inconsistent. However, in most studies, body composition was assessed using body mass index (BMI) alone, thus neglecting the presence and distribution of adipose tissue. Therefore, we aimed to investigate the impact of body and visceral fat on COVID-19 outcomes. Methods: Observational, prospective cohort study included 216 consecutive COVID-19 patients hospitalized at University Clinical Center Kragujevac (Serbia) from October to December 2021. Body composition was assessed using the BMI, Body fat percentage (%BF), and Visceral fat (VF) via bioelectrical impedance analysis (BIA). In addition to anthropometric measurements, variables in the research were socio-demographic and medical history data, as well as admission inflammatory biomarkers. Primary end-points were fatal outcome and intensive care unit (ICU) admission. Results: The overall prevalence of obesity was 39.3% according to BMI and 50.9% according to %BF, while 38.4% of patients had very high VF levels. After adjusting odds ratio values for cofounding variables and obesity-related conditions, all three anthropometric parameters were significant predictors of primary end-points. However, we note that %BF and VF, compared to BMI, were stronger predictors of both mortality (aOR 3.353, aOR 3.050, and aOR 2.387, respectively) and ICU admission (aOR 7.141, aOR 3.424, and aOR 3.133, respectively). Conclusion: Obesity is linked with COVID-19 mortality and ICU admission, with BIA measurements being stronger predictors of outcome compared to BMI use alone.